Serological Surveillance of Betacoronaviruses in Bat Guano Collectors: Pre-COVID-19 Pandemic and Post-SARS-CoV-2 Emergence - Sasiprapa Ninwattana; Spencer L. Sterling; Khwankamon Rattanatumhi; Nattakarn Thippamom; Piyapha Hirunpatrawong; Pakamas Sangsub; Thaniwan Cheun-Arom; Dominic Esposito; Chee Wah Tan; Wee Chee Yap; Feng Zhu; Lin-Fa Wang; et al. (Viruses, 2025)
Community-based serosurveillance for emerging zoonotic viruses can provide a powerful and cost-effective measurement of cryptic spillovers. Betacoronaviruses, including SARS-CoV, SARS-CoV-2 and MERS-CoV, are known to infect bats and can cause severe respiratory illness in humans, yet remain under-surveyed in high-risk populations. This study aimed to determine the seroprevalence of betacoronaviruses in an occupational cohort in contact with bats before and after the emergence of SARS-CoV-2. Serum samples from pre- and post-COVID-19 pandemic were screened using antigen-based multiplex microsphere immunoassays (MMIAs) and a multiplex surrogate virus neutralization test (sVNT). Pre-pandemic samples showed no SARS-CoV-2 antibodies, while post-pandemic samples from vaccinated participants displayed binding and neutralizing antibodies against SARS-CoV-2 and a related bat CoV. Furthermore, one participant (1/237, 0.43%) had persistent antibodies against MERS-CoV in 2017, 2018 and 2021 but was seronegative in 2023, despite reporting no history of traveling abroad or severe pneumonia. The observed sustained antibody levels indicate a possible exposure to MERS-CoV or a MERS-CoV-like virus, although the etiology and clinical relevance of this finding remains unclear. Ongoing surveillance in high-risk populations remains crucial for understanding virus epidemiology and mitigating zoonotic transmission risk.